Coordination assemblies of seven metal-organic frameworks based on a bent connector: structural diversity and properties1. Issue 16 (28th April 2015) - Song, Bai-Qiao; Qin, Chao; Zhang, Yu-Teng; Wu, Xue-Song; Liu, Hong-Sheng; Shao, Kui-Zhan; Su, Zhong-Min
<x xml:space="preserve">Abstract</x> Seven new metal–organic frameworks were prepared, showing structural characters of interpenetration, self-penetration, interdigitation, polythreading, and single- and triple-stranded helical chains.